Building codes illustrated a guide to understanding the 2015 international building code® - Ching, Francis D. K. 1943-; Winkel, Steven R.; International Code Council (Hoboken, New Jersey John Wiley & Sons, Inc., 2016)
Building Codes Illustrated: A Guide to the 2015 International Building Code, Fifth Edition is a bestselling complement to the International Building Code, or IBC. Designed to give you an insider's look at the origins of the IBC, how it can be interpreted, and how it applies to design and construction, this updated text offers new information regarding hazmat occupancies, hospitals, and nursing homes, major changes to how building heights and areas are presented, as well as means of egress, and the latest information on building materials, interior environments, and structural provisions. Francis D.K. Ching's distinctive illustrations and the code expertise of Steven Winkel, FAIA, give students and professionals in architecture, interior design, construction, and engineering industries a user-friendly, easy-to-use guide to fundamentally understanding the 2015 IBC.
Building codes -- Navigating the code -- Use and occupancy -- Special uses and occupancies -- Building heights and areas -- Types of construction -- Fire-resistive construction -- Interior finishes -- Means of egress -- Accessibility -- Interior environment -- Energy efficiency -- Exterior walls -- Roof assemblies -- Structural provisions -- Special inspections and tests -- Soils and foundations -- Building materials and systems -- Existing structures.
"ICC, International Code Council"--Cover.
Includes bibliographical references (page 423-424) and index.
Keywords: Standards, Engineering; Buildings -- Specifications